A single-/double-perovskite composite with an overwhelming single-perovskite phase for the oxygen reduction reaction at intermediate temperatures - Chen, Y.; Shen, J.; Yang, G.; Zhou, W.; Shao, Zongping (R S C Publications, 2017)
The cathode is a key part in solid oxide fuel cells (SOFCs) that largely determines the cell power output and lifetime, and consequently the competitiveness of this attractive technology. Thus, the catalysts for cathodes with high electro-catalytic activity and good stability for the oxygen reduction reaction (ORR) at the intermediate temperature range are vital. Herein, a single-perovskite (SP)/double-perovskite (DP) composite with the nominal composition of SrCo 0.7 Fe 0.2 W 0.1 O 3-d is designed. During the synthesis, a slightly W-doped SP and a W-rich B-site cation ordered DP with the dominant SP phase of approximately 80 wt% are formed simultaneously. This new composite shows obviously enhanced stability owing to the W doping effect in the SP phase and increased activity from the synergistic effect between the SP and DP phases compared to the W-free SrCo 0.8 Fe 0.2 O 3-d perovskite. We anticipate that the synthesis of this perovskite-type composite could pave the way to discover more perovskite-based composite catalysts for SOFCs.